2021
DOI: 10.1101/2021.06.12.448118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TRAF2, an innate immune sensor, reciprocally regulates mitophagy and inflammation to maintain cardiac myocyte homeostasis

Abstract: Mitochondrial damage triggers cell death signaling with catastrophic consequences in long-lived and irreplaceable cells, such as cardiac myocytes. Sensing of leaked mitochondrial DNA upon mitochondrial damage is also a potent trigger of inflammation. Whether the innate immune response pathways monitor mitochondrial damage in mitochondria-rich cardiac myocytes to prevent inflammation and cell death, remains unknown. TRAF2, an adaptor protein downstream of innate immune receptors, localizes to the mitochondria i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 63 publications
(170 reference statements)
0
10
1
Order By: Relevance
“…Previous studies showed that TRAF2 mediates cytoprotective TNF receptor signaling in the heart during stress, and, that TRAF2, in concert with Parkin, mediates mitophagy in cardiomyocytes in response to stress. 3 By extending these findings, Ma et al 2 showed that the loss of TRAF2 function attenuated mitophagy at baseline in the adult heart, accompanied by accumulation of mitochondrial proteins and mitochondrial dysfunction. Furthermore, the loss of TRAF2 function led to stimulation of TLR9 and macrophage infiltration, apoptosis, and cardiac dysfunction, which suggested that endogenous TRAF2 protects the heart against TLR9-induced sterile infection by facilitating safe disposal of mitochondrial DNA through activation of mitophagy, even without stress.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Previous studies showed that TRAF2 mediates cytoprotective TNF receptor signaling in the heart during stress, and, that TRAF2, in concert with Parkin, mediates mitophagy in cardiomyocytes in response to stress. 3 By extending these findings, Ma et al 2 showed that the loss of TRAF2 function attenuated mitophagy at baseline in the adult heart, accompanied by accumulation of mitochondrial proteins and mitochondrial dysfunction. Furthermore, the loss of TRAF2 function led to stimulation of TLR9 and macrophage infiltration, apoptosis, and cardiac dysfunction, which suggested that endogenous TRAF2 protects the heart against TLR9-induced sterile infection by facilitating safe disposal of mitochondrial DNA through activation of mitophagy, even without stress.…”
mentioning
confidence: 87%
“…In this issue of JACC: Basic to Translational Science , using conditional cardiac-specific TRAF2 knock-out (KO) mice, Ma et al 2 showed that TNF-receptor−associated factor 2 (TRAF2), a mitochondrially localized E3 ubiquitin ligase, mediates mitophagy, and therefore plays a protective role in the adult heart at baseline. Previous studies showed that TRAF2 mediates cytoprotective TNF receptor signaling in the heart during stress, and, that TRAF2, in concert with Parkin, mediates mitophagy in cardiomyocytes in response to stress.…”
mentioning
confidence: 99%
See 3 more Smart Citations